Determination of the mass transfer coefficient of ammonia emissions from dairy open lots using a scale model. (February 2020) - Ding, Luyu; Li, Qifeng; Wang, Chaoyuan; Zhang, Guoqiang; Jiang, Ruixiang; Yu, Ligen; Zheng, Wengang; Gao, Ronghua; Ma, Weihong; Zhang, Shirui; Shi, Zhengxiang
Abstract : Open lots are commonly used to provide outdoor free ranging spaces for dairy cows in many countries such as China and the USA. For this type of operation, the manure characteristics, floor types and environmental conditions, which potentially affect gaseous emissions from manure, are quite different from those of indoor systems. The estimation of NH3 emissions from manure depends greatly on the mass transfer coefficient, an empirical constant determined by environmental factors in the process-based emission model. Using a scale model, this study measured ammonia emissions to be expected from dairy open lots, based on different combinations of different surface air velocities (0.6–2.2 m s −1 ), air temperatures (15–35 °C) and relative humidity values (20–60%). Based on the two-film theory, the overall mass transfer coefficient ( K OL ) of NH3 was calculated from directly measured NH3 emission rates and the ammonium nitrogen content, temperature, and pH of manure. As an indicator of the driving potential of gaseous volatilisation, the vapour pressure deficit ( VPD ) was estimated using air temperature and relative humidity. As the VPD and surface air velocity increased, the measured NH3 emission rates ranged from 1.35 to 19.18 mg kg −1 h −1, and the estimated K OL of NH3 from dairy open lots was within the range of 1.48 × 10 −6 – 7.86 × 10 −6 m s −1 . Using the air velocity and VPD as variables, a non-linear empirical model was developed to estimate the K OL for NH3 emissions from manure on dairy open lots ( R 2 = 0.69). The normalised mean error of the model was approximately 19.4%. Highlights: Overall mass transfer coefficient ( K OL ) was estimated based on two-film theory. K OL of NH3 emission was in the range of 1.48–7.86 10 −6 m s −1 from dairy open lots. Air vapour pressure deficit ( VPD ) was positively related to NH3 emission and K OL . A nonlinear model was obtained to estimate K OL using air velocity and VPD.